Da invisibilidade à representação: uma análise das desconstruções de gênero em a Lei do desejo, de Pedro Almodóvar - Brod, Marta (2016)
This thesis aims to analyze the film Law of Desire, from Spanish director Pedro Almodóvar, from the perspective of gender studies and the relations of binary deconstruction. For this, five scenes were selected to represent the characters in the film living with their sexuality and identity chosen gender. This analysis will be made from the discussions of gender studies and queer theory. The work also brings a historic introduction of the new queer cinema and the emergence of LGBT characters in regard to American and European cinema. To understand the analysis, a reading of the entire filmography of Pedro Almodóvar was taken through the exploratory research methodology.